2017
DOI: 10.1089/neu.2016.4577
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Strategies after Spinal Cord Injury: Inquiry into the Mechanisms of Success and Failure

Abstract: Body-weight supported locomotor training (BWST) promotes recovery of load-bearing stepping in lower mammals, but its efficacy in individuals with a spinal cord injury (SCI) is limited and highly dependent on injury severity. While animal models with complete spinal transections recover stepping with step-training, motor complete SCI individuals do not, despite similarly intensive training. In this review, we examine the significant differences between humans and animal models that may explain this discrepancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 279 publications
(312 reference statements)
1
56
0
Order By: Relevance
“…Similar muscle activation patterns were also observed at t7 and t8. While the mechanisms underlying this motor recovery are currently unclear, a recent review by Cote and colleagues 43 supports the view that humans are particularly dependent on residual descending input to generate stepping and standing, and that the human lumbosacral spinal circuitry is more depressed after a severe SCI, compared to other mammals. This assumption is also empirically supported by the fact that tonic, near-motor threshold lumbosacral scES aimed at mimicking the supraspinal tonic drive to the lumbosacral spinal circuitry enabled the generation of motor patterns effective for standing in individuals with chronic, motor complete SCI 17 , 18 .…”
Section: Discussionmentioning
confidence: 94%
“…Similar muscle activation patterns were also observed at t7 and t8. While the mechanisms underlying this motor recovery are currently unclear, a recent review by Cote and colleagues 43 supports the view that humans are particularly dependent on residual descending input to generate stepping and standing, and that the human lumbosacral spinal circuitry is more depressed after a severe SCI, compared to other mammals. This assumption is also empirically supported by the fact that tonic, near-motor threshold lumbosacral scES aimed at mimicking the supraspinal tonic drive to the lumbosacral spinal circuitry enabled the generation of motor patterns effective for standing in individuals with chronic, motor complete SCI 17 , 18 .…”
Section: Discussionmentioning
confidence: 94%
“…One of the possible explanations lies in the association between locomotor training and FES that may have facilitated a possible conversion of type II bers to type I (Côté et al, 2017). This is essential for postural support while standing (Postans et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, neuronal plasticity, owing to neurogenesis, gene activation, dendritic modi cations, and changes in physiological properties, as well as glial and vascular plasticity (Wolpaw, 2010) probably to some degree also promote the restoration of motor function secondary to sodium-channel voltage activation (Wolpaw, 2007). This type of step-training increases the e cacy of synaptic connections from residual descending pathways to interneurons located near the lesion (Côté et al, 2017). Therefore, the use of multidisciplinary approaches may improve the functionality (Gomes-Osman et al, 2016; Gant et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in both passive and active electrophysiological MN properties indicate a reduction in MN excitability in cats (Cope et al 1986;Czéh et al 1978;Hochman and McCrea 1994) and rats (Beaumont et al 2004(Beaumont et al , 2008Button et al 2008;MacDonell et al 2012). On the other hand, there is an increase in spastic contractions that may reflect the activation of PIC (Bennett et al 2001a(Bennett et al , 2001bCôté et al 2017), which would enhance MN excitability or polysynaptic reflexes. While PICs contribute to spasticity development (Brocard et al 2016), other mechanisms have also been shown to contribute to spastic contractions such as decrease in the H-reflex postactivation depression (Lamy et al 2009) and downregulation of the potassium-chloride transporter KCC2 (Boulenguez et al 2010).…”
Section: Spinal Cord Injurymentioning
confidence: 99%